Penggunaan Mordan Akhir Terusi terhadap Hasil Celupan Kain Batik dengan Ekstrak Kayu Secang - Dwi Suheryanto (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Batik cloth color durability is a prerequisite for improving the competitiveness of the product, as the number of consumer complaints on the subject. How many treatments that can be done to address and improve fastness, is to perform the process of perfecting the end of the fabric that has been dyed using the final mordant materials, namely “terusi” or cupric sulfate (CuSO4) .5H2O. The use of extracts of the wooden cup on a batik cloth, batik cloth produces the erosion resistance value is low, so it is rarely used in the singular in batik dyeing, but mixed with wood extract Cleaner or other materials, but the results did not show its true colors. The purpose of this activity is to improve the quality of batik cloth with increased power results dye color fastness. The materials used, namely cotton fabric primisima, silk fabric T56, wax batik, wood shavings cup, alum, and cupric sulfate, as for the procedure include, extract manufacture wooden cup (1:8), mordant early cotton cloth with alum, batik dyeing with extract solution wooden cup, then made the final refinement using variation cupric sulfate concentration, that is 15 g/l, 20 g/l, and 25 g/l, wax removing, and test color fastness. From the results of the test color fastness to washing, good value at terusi concentration of 25 g / l is 4-5, with a strong color intensity values (the most powerful), the wave had a value of 26 with a length of 0.6637.